PENERAPAN MODEL KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR PASSING SEPAK BOLA PADA SISWA KELAS X SMK WERDHI SILA KUMARA - I Made Darmada; Komang Gede Taman Sastra Wiguna (Widyadari, 2025)
This study aims to determine the effectiveness of implementing the cooperative learning model Student Teams Achievement Division (STAD) in improving the learning outcomes of basic passing techniques in football among Grade X students of SMK Werdhi Sila Kumara. This research is a Classroom Action Research (CAR) conducted in two cycles, referring to the Kemmis and McTaggart model, which includes four stages: planning, action, observation, and reflection. The subjects of the study were students of Grade X in the 2024/2025 academic year. Data were collected through observation and skill assessments using a structured evaluation instrument. The pre-action results showed that the average final score of students was 55.41, with only 3 out of 37 students achieving the minimum mastery criterion. After applying the STAD learning model, a significant improvement was observed in Cycle I, where the average score increased to 77.03, and the number of students achieving mastery rose to 33. These results indicate that the STAD model fosters a more active, collaborative, and engaging learning environment, leading to improved mastery of basic football passing skills. Therefore, it can be concluded that the implementation of the cooperative learning model STAD is effective in enhancing the learning outcomes of football passing techniques among Grade X students at SMK Werdhi Sila Kumara.